Secondary Bacterial Infection and Clinical Characteristics in Patients With COVID-19 Admitted to Two Intensive Care Units of an Academic Hospital in Iran During the First Wave of the Pandemic - Pourajam, Samaneh; Kalantari, Elham; Talebzadeh, Hamid; Mellali, Hamid; Sami, Ramin; Soltaninejad, Forogh; Amra, Babak; Sajadi, Mahdi; Alenaseri, Malihe; Kalantari, Forough; Solgi, Hamid (Frontiers in Cellular and Infection Microbiology, 2022)
Data on the prevalence of bacterial co-infections among adults with COVID-19 admitted to the intensive care unit (ICU) are rare. We aimed to determine the prevalence of bacterial co-infection, antibiotic use and clinical characteristics in patients admitted to the ICU with severe SARS-CoV-2 pneumonia. This was a retrospective cohort study of adults with severe COVID-19 admitted to two ICUs from 6 March to 7 September 2020 at an academic medical centers in Isfahan, Iran. To detect COVID-19, reverse transcription real-time polymerase chain reaction was performed. Data collection included patient’s age, gender, main symptoms, history of underlying disease, demographics, hospital stay, outcomes and antibiotic regimen. Antimicrobial susceptibility testing was carried out according to the CLSI guidelines. During the study period, 553 patients were referred to the both ICUs for COVID-19 with severe pneumonia. Bacterial co-infection was detected in 65 (11.9%) patients. The median age was 69.4 (range 21-95) years; 42 (63.6%) were males. Notably, 100% (n = 65) of the patients with bacterial co-infection were prescribed empirical antibiotics, predominantly meropenem (86.2%) with a median duration of 12 (range 2-32) days and levofloxacin (73.8%) with a median duration of 9 (range 2-24) days. The most prevalent causative agents for bacterial co-infection were K. pneumoniae (n = 44) and A. baumannii (n = 33). The most patients with bacterial co-infection showed extensive drug-resistance. The overall mortality rate was 83% (54/65). We found a high prevalence of carbapenem resistant gram-negative bacteria in COVID-19 patients admitted to our ICUs, with a high proportion of K. pneumoniae. These findings emphasise the importance of implementation of infection prevention and control of programs and highlight the role of antimicrobial stewardship during a pandemic.